S100 Protein Family in Lung Cancer: an Updated Narrative Review - Wang T; Liu R (Cancer Management and Research)
Ting Wang, Rui Liu Department of Respiratory Medicine, Xi’an People’s Hospital (Xi’an No.4 hospital), Xi’an, 710004, People’s Republic of ChinaCorrespondence: Rui Liu, Department of Respiratory, Xi’an People’s Hospital (Xi’an No.4 hospital), No. 21 Jiefang Road, Xi’an City, Shaanxi Province, 710004, People’s Republic of China, Tel/Fax +86-18966721169, Email mafada@126.comAbstract: The S100 protein family comprises 25 known members that modulate variously basic biological behaviors of cells by binding Ca2+ and activating Ca2+-signaling pathways. As the primary cause of cancer-related death, lung cancer is closely associated with several S100 proteins, like S100A2, S100A4, S100A6, S100A8/9, etc. Notably, the functions and mechanisms of different S100 proteins vary in every sub-type of lung cancer. Overall speaking, the abnormal expression of S100 proteins is predominantly observed in lung adenocarcinoma, while their roles are limited in small-cell lung cancer. This review, which presents an update on our previously published review of S100 proteins in lung cancer (2021), aims to enable readers having a deeper understanding of the roles of different S100 proteins in three main sub-types of lung cancer, as well as to facilitate their future researches. It focuses on relevant studies examining the functions of S100 proteins in lung adenocarcinoma, squamous carcinoma, and small-cell lung cancer. This review was conducted based on this standard, and provides a comprehensive evaluation of the literature review on S100 proteins as well as enhances understanding of the relationship between S100 proteins and every sub-type of lung cancer from a new perspective.Keywords: S100 protein family, lung cancer, adenocarcinoma, squamous carcinoma, small cell lung cancer